The application of the rule of “avoiding hudud due to shubhah” as a mechanism for ensuring justice in the determination of punishments in Islamic criminal law - Hussin, Nasimah; Zawawi, Majdah (2013)
There are strict evidentiary requirements that need to be fulfilled before a person can be found guilty in a court of law. The avoidance of infliction of punishment of hudud where there exists a situation called shubhah (doubt) is based on the Hadith of Prophet s.a.w. which says, "Set aside the execution of hudud punishments in cases of doubt (shubhah)." The rule of avoiding hudud due to shubhah not only applies to hudud cases, but it can also be applied in qisas and ta'zir crimes. This is because the main aim of the principle is to maintain justice and to guarantee that the rights of the accused are protected. This paper looks at the meaning of shubhah, its types and discusses how this concept has been used to ensure that the application of punishment is done in a practical manner. This paper also examines the practice of Shari’ah Courts in Malaysia when considering shubhah in the determination of punishment. It is submitted that the existence of shubhah can be used as a mechanism to ensure that the application of punishments are not issued at the whims and fancies of the judges. This clearly shows that the operation of the Islamic criminal justice system operates in moderation and looks into the welfare of not only the victim but also balances it with the rights of the accused persons.